Investigation of the Effects of Cement Dust Pollution on the Environment using Biomonitor Organism - ÖZYİĞİT, İBRAHİM İLKER (My University, 2022)
This research was carried out in the vicinity of Kant Cement Plant located in Issyk-Ata district, Cuy region of Kyrgyzstan. Kant Cement Plant produces approximately 600,000-700,000 tonnes of cement per year. Because of the cement production, a large amount of cement dust release containing some heavy metals and other toxic substances occurs in the nearby environment. The aim of our research was to investigate the negative effects of the cement dust spreading around on living organisms. In this research, the reed plant (Phragmites australis L.) was used as a study material to determine the rate pollution observed nearby Kant via the detection of heavy metal and nutrient element contents (Al, Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb and Zn) of the collected plant and co-located soil samples using ICP-OES. Also, the total chlorophyll contents in the leaves of the plant samples was measured using CCM-200 plus (Opti-Sciences). The lowest and highest heavy metal and mineral element contents of the plant samples (in mg kg1 ) were found to be as: 119.30 (in stems) and 3908.11 (in roots) for Al in stations 9 and 6; 12.52 (in stems) and 47.88 (in unwashed leaves) for B in control (1) and station 6; 3432.38 (in stems) and 10120.64 (in roots) for Ca in control (1) and station 6; 125.95 (in washed leaves) and 87.38 (in stems) for Cd in control (1) and station 6; 6.74 (in stems) and 24.56 (in roots) for Cr in control (1) and station 6; 3.92 (in stems) and 28.13 (in unwashed leaves) for Cu in control (1) and station 6; 303.82 (in stems) and 1100.86 (in unwashed leaves) for Fe in control (1) and station 6; 5334.55 (in stems) and 23789.68 (in unwashed leaves) for K in control (1) and station 6; 692.44 (in stems) and 3352.71 (in unwashed leaves) for Mg in control (1) and station 6; 33.94 (in stems) and 391.22 (in roots) for Mn in control (1) and station 6; 162.30 (in stems) and 709.03 (in unwashed leaves) for Na in control (1) and station 6; 3.5 (in stems) and 19.61 (in roots) for Ni in control (1) and station 6; 2.25 (in stems) and 20.41 (in unwashed leaves) for Pb in control (1) and station 6; and 35.94 (in stems) and 147.65 (in roots) for Zn in control (1) and station 6, respectively. The lowest and highest heavy metal and mineral element contents of the soil samples (in mg kg-1 ) were found to be as: 30034.07 and 38334.45 for Al in stations 9 and 6; 39.61 and 80.32 for B in control (1) and station 6; 11832.33 and 23922.33 for Ca in control (1) and station 6; 165.38 and 1457.8 for Cd in control (1) and station 6; 20.79 and 42.29 for Cr in control (1) and station 6; 14.8 and 45.84 for Cu in control (1) and station 6; 17390.18 and 35158.99 for Fe in control (1) and station 6; 10230.83 and 20684.6 for K in control (1) and station 6; 4356.34 and 8807.68 for Mg in control (1) and station 6; 598.38 and 1210.04 for Mn in control (1) and station 6; 1163.76 and 2353.09 for Na in control (1) and station 6; 27.68 and 56.16 for Ni in control (1) and station 6; 18.47 and 77.94 for Pb in control (1) and station 6; and 136.29 and 275.73 for Zn in control (1) and station 6, respectively. When the results obtained from our work were compared with the controls, it showed that the Cement plant in Kant cause pollution in nearby environment by the way of releasing heavy metals including Cd, Cr, Pb and Ni (partially). Kyrgyzstan is a country recently showing an increasing growth trend. As a result of high rate of urbanization following of economic and industrial development, Kyrgyzstan encounters with the problems related with pollution. From our work, the recommendation to the local authorities to take necessary precautions before the pollution reaching dangerous levels. By our work, the recommendation would be to the local authorities to take necessary precautions before the pollution reaching dangerous levels. Keywords: Phragmites australis, Biomonitoring, Heavy Metal Pollution, Cement Dust, Kant
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Phragmites australis; Biomonitoring; Heavy Metal Pollution; Cement Dust; Kant